South Asian Historiography from the British Period to Today - Jayaneththi, Ramesha (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This essay descriptively evaluates the South Asian historiography from British colonial times to today, showing how changing ideas, shifting politics, and fierce debates over knowledge have shaped the field. In the nineteenth century, colonial scholars and administrators used Orientalist philology, utilitarian critiques, administrative surveys, and thick codification manuals to shape narratives of South Asia’s past. By the early twentieth century, nationalist historians turned history into a weapon against colonial rule, shaping stirring tales of ancient Hindu glory. After independence, the field branched out and new historical methods were adopted and new theories were used under revisionist historians. In India, Marxist historians brought in structural analysis, agrarian studies, and materialist methods, while the Cambridge School recast politics around local favors and rivalries among the elite. Starting in the 1980s, Subaltern Studies and feminist historians reshaped the field, turning attention toward peasants in fields, factory workers, women, and others long pushed to the margins. By turning to unexpected sources and postcolonial theory, these scholars laid bare the elitism woven through colonial and nationalist histories and challenged the deep-set assumptions about knowledge.